Disseminated cerebellar hemangioblastoma in two patients without von Hippel–Lindau disease - Akimoto, Jiro (Medknow Publications & Media Pvt Ltd, 2014)
BACKGROUND: Two patients who had received a total resection of cerebellar hemangioblastoma developed cerebrospinal fluid dissemination during a long-term follow-up period. We present this rare disease with discussion based on the literature. CASE DESCRIPTION: The patients were two women aged 45 and 57 years. In the cerebellar hemisphere, one patient had cystic hemangioblastoma of mural nodule type and the other had solid type. Both the patients successfully underwent total resection by craniotomy. They presented no mutations in the von Hippel-Lindau disease (VHL) gene or lesions in the other organs. One patient developed local recurrence 38 months after the initial surgery, and received stereotactic radiosurgery. Three spinal cord tumors developed 91 months later, and the tumors were disseminated to the entire cerebrospinal cavity 107 months later. The other patient developed hydrocephalus 53 months after the initial surgery with tumor tissues disseminated in the intracranial subarachnoid space. The conditions of the two patients gradually aggravated despite treatment with ventriculo-peritoneal shunt and irradiation to the whole brain and whole spinal cord. CONCLUSION: Cerebrospinal fluid dissemination of cerebellar hemangioblastoma was found dominantly in non-VHL patients. The diagnosis was made 10 years after the initial surgery. Irradiation therapy was performed, but the patients died about 2 years after the diagnosis was given. Molecular targeted therapies including vascular proliferation suppression have been attempted lately, but no effective therapy has been established. Early diagnosis of dissemination as well as combination of aggressive excision and stereotactic radiosurgery are considered to be appropriate for current interventions.